2017
DOI: 10.1155/2017/1836960
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Optimal Bone Marrow Site for the Isolation of Porcine Mesenchymal Stem Cells

Abstract: Background. One of the most plentiful sources for MSCs is the bone marrow; however, it is unknown whether MSC yield differs among different bone marrow sites. In this study, we quantified cellular yield and evaluated resident MSC population from five bone marrow sites in the porcine model. In addition, we assessed the feasibility of a commercially available platelet concentrator (Magellan® MAR01™ Arteriocyte Medical Systems, Hopkinton, MA) as a bedside stem cell concentration device. Methods. Analyses of bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 63 publications
2
22
0
1
Order By: Relevance
“…It is clear that both unfractionated bone marrow or specific subpopulation of mesenchymal stem cells can be applied in stem cell therapy [65][66][67][68]. The isolation of BMSCs has been developed and used to characterize mesenchymal stem cells in mouse, rabbit, dog, pig, rat, and human [69][70][71][72][73][74]. Hematopoietic stem cells (HSCs) and mesenchymal stem cells, which localized together in the bone marrow, are most commonly used in clinical application.…”
Section: Processes In Isolation Of Bmscsmentioning
confidence: 99%
“…It is clear that both unfractionated bone marrow or specific subpopulation of mesenchymal stem cells can be applied in stem cell therapy [65][66][67][68]. The isolation of BMSCs has been developed and used to characterize mesenchymal stem cells in mouse, rabbit, dog, pig, rat, and human [69][70][71][72][73][74]. Hematopoietic stem cells (HSCs) and mesenchymal stem cells, which localized together in the bone marrow, are most commonly used in clinical application.…”
Section: Processes In Isolation Of Bmscsmentioning
confidence: 99%
“…In humans, the most common anatomical location to obtain BM is the iliac crest, but other BMA sites have been utilized ( Table 2). Recently, McDaniel and co-workers, using a porcine model, reported that all studied anatomical bone marrow harvesting locations contained MSCs but the iliac crest was the most abundant source of MSCs [10]. These findings were confirmed in a clinical study, where MSCs were found in BM acquired from the metaphysis of the distal femur, the proximal tibia, and iliac crest.…”
Section: Bone Marrow Aspiration Anatomical Sitesmentioning
confidence: 70%
“…In adults, the red bone marrow is a rich source of bone marrow-derived cells and present in most skeletal system bones of the iliac crest, tibia, spine vertebrae, humerus, calcaneus, ribs, and near point of attachment of long bones of legs and arms. In this wellshielded environment, an estimate of 500 billion cells per day can be produced, in particular erythrocytes, granulocytes, and platelets [10]. Regenerative medicine applications have a focus on the use of the red bone marrow as it contains myeloid and lymphoid stem cells and MSCs.…”
Section: Red and Yellow Bone Marrowmentioning
confidence: 99%
“…Gene expression was normalized to ACTG1, B2M, and GAPDH, and the fold change in expression was determined by the 2 −ΔΔ C T method. pASCs were compared with a previously characterized line of bone marrow stem cells (BMSCs) for stem cell/differentiation marker expression .…”
Section: Methodsmentioning
confidence: 99%